S-Adenosylhomocysteine is a useful metabolic factor in the early prediction of septic disease progression and death in critically Ill patients: a prospective cohort study - Centner, Franz-Simon; Schöttler, Jochen; Brohm, Kathrin; Mindt, Sonani; Jäger, Evelyn; Hahn, Bianka; Fuderer, Tanja; Lindner, Holger A.; Schneider-Lindner, Verena; Krebs, Jörg; Neumaier, Michael; Thiel, Manfred (International journal of molecular sciences, 2023)
A common final pathway of pathogenetic mechanisms in septic organ dysfunction and death is a lack or non-utilization of oxygen. Plasma concentrations of lactate serve as surrogates for the oxygen-deficiency-induced imbalance between energy supply and demand. As S-adenosylhomocysteine (SAH) was shown to reflect tissue hypoxia, we compared the ability of SAH versus lactate to predict the progression of inflammatory and septic disease to septic organ dysfunction and death. ...
Gesehen am 20.12.2023